AUTHENTIC LEADERSHIP AND ITS IMPACT ON SUSTAINABLE PERFORMANCE "AN ANALYTICAL STUDY OF THE OPINIONS OF A SAMPLE OF EMPLOYEES OF THE STATE COMPANY FOR GRAIN TRADE" - ABBAS HUSSEIN AL-ZIYADI, SAHAR; ISMAIL AL-HUSSEIN, HUSSEIN (Iraqi Journal for Administrative Sciences, 2024)
The research aims to test the relationship of the influence of the original leadership on sustainable performance as a variable in the General Company for Grain Trading / Baghdad, based on the importance of the research topic in public organizations and the role that these organizations have in society, the researcher adopted the descriptive and analytical approach in the completion of the current research by collecting data from A director sample of departments, divisions and units totaled (269) respondents, based on the questionnaire form (after verifying its validity and reliability), which included (28) paragraphs prepared according to ready-made standards for foreign and Arab studies, supported by personal interviews and field observations, for the independent variable of the original leadership Self-awareness, ethical perspective, balanced treatment, and relationship transparency); And the independent variable of sustainable performance (economic, social, environmental dimension). The research started from a problem represented by a main question: What is the role of original leadership in the sustainable organizational performance of the General Company for Grain Trade? The researcher relied on the appropriate statistical analysis tools available in the SPSS and Amos programs to test the main research hypotheses. The most prominent finding of the research is the growing influence of original leadership on sustainable performance